Espiritualidade, religiosidade e sentido do sofrimento em mulheres em tratamento oncológico de mama: um estudo exploratório - Patrício, Ana Clara de Andrade (2023)
Spirituality and religiosity play a significant role in the journey of women who face the challenge of breast cancer. For many of them, the search for meaning in the suffering caused by this illness is a fundamental part of their experience. Through connecting with their spiritual and religious beliefs, these women find emotional support, inner strength and a path to acceptance and understanding of their condition. Therefore, the research question that guided this dissertation was: do the spirituality and religiosity experienced by women with breast cancer help them to discover meaning in the suffering resulting from this disease? That way, the present dissertation had the general objective of understanding how the spirituality and religiosity experienced by women with breast cancer support them to discover meaning in the suffering arising from this disease. Therefore, a scope review, a systematic review and a qualitative study were carried out. Study 1 aimed to map the scientific productions in the area of Religious Sciences on the implications of spirituality and religiosity in the health of cancer patients. For eligibility criteria, scientific productions in the format of articles, dissertations and theses, published from January 1st, 2018 to October 30th, 2022 in magazines A1, A2, B1 and B2 from the area of Sciences of Religion and Theology were considered, and in the catalog of theses and dissertations of postgraduate programs in CR at CAPES, written in Portuguese (Brazil), English, Spanish, German, Italian or French and that brought spirituality and religiosity in health as their central theme of oncology patients health. From the 1669 studies found, 9 were selected for full reading, resulting in a final sample of 8 analyzed studies. The results of this review showed that the spirituality and religiosity experienced by cancer patients help them in coping with the disease, in psychological well-being, in the perception of meaning in existence and in quality of life. Study 2 aimed to identify, synthesize and evaluate the literature using a qualitative method regarding spirituality as a strategy for coping with female breast cancer. The search for data took place in SciELO, PePSIC, PsycINFO, Medline, ERIC and PubMed, which traditionally index research in the areas of health, psychology, psychiatry and education. For eligibility criteria, articles published in the period from January 1st, 2018 to March 31th 2023, without language restrictions, using a qualitative approach and which discussed the perception of women with breast cancer about spirituality and religiosity were considered as strategies for confrontation with this disease. Of the 906 articles found, 6 remained in the final stage. The results provided evidence that spirituality and religiosity are resources that can be used among patients with breast cancer, because it allows them to see a new meaning in the experience of illness and treatment. Finally, study 3 aimed to comprehend how the spirituality and religiosity experienced by women with breast cancer help them to discover meaning in the suffering resulting from this disease. Participated in the study 10 women with breast cancer, aged between 42 and 82 years (M = 58.6; SD = 11.60), who were aware of the diagnosis and were undergoing treatment at a hospital in Campina Grande. - PB. Therefore, they answered a biosociodemographic questionnaire and orally reported their life stories with breast cancer. Through content analysis, it was possible to verify that the following three themes emerged from the participants' speeches: discovery of breast cancer; coping with the disease; and, look up. In view of this, a perception is understood that spirituality and religiosity helped them in coping with breast cancer, as they made them change them attitudes in the face of questions about the suffering arising from the disease and see a meaning. In short, it is concluded that spirituality and religiosity contribute to the discovery of meaning in the inevitable suffering of women with breast cancer.